(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
This article is written as a basis for the evaluation of the administration of the shariah criminal justice. The administration of shariah criminal justice must be anchored on the Quran and the sunnah and administered for the sake of success in this world and the hereafter. This basis may be determined by looking at the main objectives of the Shariah, also known as maqasid al-shari’ah (high intent of law). To uphold justice is one of the basic objectives of Shariah, and requires the appointment of judges who are steadfast in their faith as well as knowledgeable in the shariah. This article concludes that truth and justice must be based on the Islamic mould, and that it is necessary to ensure that the administration of shariah criminal justice follows this mould. Keywords: administration of justice, maqasid, fundamental rights, investigation, punishment